2016
DOI: 10.1016/j.jes.2015.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic redox transformation by Pseudomonas sp. HN-2 isolated from arsenic-contaminated soil in Hunan, China

Abstract: A mesophilic, Gram-negative, arsenite[As(III)]-oxidizing and arsenate[As(V)]-reducing bacterial strain, Pseudomonas sp. HN-2, was isolated from an As-contaminated soil. Phylogenetic analysis based on 16S rRNA gene sequencing indicated that the strain was closely related to Pseudomonas stutzeri. Under aerobic conditions, this strain oxidized 92.0% (61.4 μmol/L) of arsenite to arsenate within 3 hr of incubation. Reduction of As(V) to As(III) occurred in anoxic conditions. Pseudomonas sp. HN-2 is among the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…This behaviour can also be extended to the genera Cupriavidus (Zhang et al, 2009;Estrada-de los Santos et al, 2011), Pseudomonadales (Zhang et al, 2016),…”
Section: Bacteriamentioning
confidence: 83%
“…This behaviour can also be extended to the genera Cupriavidus (Zhang et al, 2009;Estrada-de los Santos et al, 2011), Pseudomonadales (Zhang et al, 2016),…”
Section: Bacteriamentioning
confidence: 83%
“…To cope with the As toxicity, As resistance (ars) genes can be found in the genome of nearly every bacterial species sequenced to date [43], and both, bacteria and fungi have the ability to tolerate As by several mechanisms including valence transformation, extra and intracellular precipitation, active uptake and biosorption [44]. Several studies have shown that the genera Pseudomonas [45,46] can reduce or oxidize arsenic and Tsubouchi and Kaneko [47] showed that Brevundimonas possess the ars operon that allow them to tolerate As by reduction or oxidation, among other processes. In regard to the fungi used in our study, there is no information about how arsenics metabolize.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted to explore different ways of transforming or removing As. Such studies have also been widely carried out by using bacteria as many exhibit As resistance, transformation and detoxification (Kao et al 2013;Ghosh et al 2015;Bagade et al 2016;Zhang et al 2016). Few studies have reported arsenic transformation along with biofilm parameters.…”
Section: Discussionmentioning
confidence: 99%